Respuesta :
Use PEMDAS and the distributive property to solve this problem-
3(x+2)-2(x+1)=8
(3 times x and 3 times 2)
3x+6-2(x+1)=8
(-2 times x and -2 times 1)
3x+6-2x-2=8
Combine like terms (3x/-2x and 6/-2)
x+4=8
Subtract 4 from both sides
x=4
3(x+2)-2(x+1)=8
(3 times x and 3 times 2)
3x+6-2(x+1)=8
(-2 times x and -2 times 1)
3x+6-2x-2=8
Combine like terms (3x/-2x and 6/-2)
x+4=8
Subtract 4 from both sides
x=4
3(x+2)-2(x+1)=8
you distribute the 3 to the numbers inside the parentheses as well as the -2 which gives you:
3x+6-2x-2=8
then you combine like terms which gives you:
x+6-2=8
then you subtract 4 from both sides to isolate x and you end up with:
x=4
Hope this helps!
you distribute the 3 to the numbers inside the parentheses as well as the -2 which gives you:
3x+6-2x-2=8
then you combine like terms which gives you:
x+6-2=8
then you subtract 4 from both sides to isolate x and you end up with:
x=4
Hope this helps!